Montreal cognitive assessment as a screening instrument for cognitive impairment in systemic lupus erythematosus patients without overt neuropsychiatric manifestations. (December 2022) - Lim, Xin Rong; Chew, Pamela Oi Khuan; Lim, Gek Hsiang; Low, Yung Ling; Lim, June Wei Ping; Ong, Huey Ni; Law, Weng Giap; Tan, Justina Wei Lynn; Thong, Bernard YH; Chia, Faith Li-Ann; Lian, Tsui Yee; Chan, Grace Yin Lai; et al.
Objectives: The Montreal Cognitive Assessment (MoCA) is an increasingly used screening tool for cognitive impairment. The aim of this study was to examine how MoCA performed in identifying cognitive impairment (CI) domains in SLE patients compared with formal standardized neuropsychological testing (NPT). Factors related to SLE disease, immunologic and psychological state associated with CI were also explored. Methods: This cross-sectional study recruited 50 SLE patients without overt neuropsychiatric manifestations from April 2017 to May 2018. The patients were evaluated with MoCA, formal NPT and the Depression, Anxiety, and Stress Scales (DASS) 42-item self-report questionnaire. Values of sensitivity and specificity were computed for different cut-offs of MoCA within each cognitive domain of NPT and descriptive analysis was used to identify the factors affecting cognitive function. Results: The median score for MoCA was 27.5 (range 22–30). Using a MoCA cutoff of <26, 18 (36%) were identified to have CI using NPT compared to 8 (16%) using MoCA. The most frequently affected cognitive domain was executive functioning with 15 affected patients. Sensitivities and specificities of the MoCA range from 50% to 100% and 5.7% to 16.7%, respectively, across cognitive domains. A lower MoCA cutoff of <25 improve sensitivity of identifying impairment in executive functioning from 60% to 80%. In univariate analysis, DASS scores, disease activity, presence of antiphospholipid antibodies, presence of concurrent autoimmune disease, current, and cumulative corticosteroid therapy did not predict cognitive performance. Conclusion: MoCA may be a useful screening tool to identify the most frequently affected cognitive domain which is executive functioning using a lower cutoff of <25 in SLE patients without overt neuropsychiatric manifestations.